Knowledge-attitude about toward sunlight exposure and lung function in construction workers - Amelia Lorensia; Rivan Virlando Suryadinata; Try Suryandi (Universitas Muhammadiyah Malang, 2020)
The primary source of Vitamin D is sunlight, which plays a role in improving respiratory health. The level of knowledge and attitudes regarding sun exposure can affect daily lifestyle, thus affecting lung function. The research design was cross-sectional and, from April to June 2018, was conducted in Rungkut District, Surabaya. The construction workers were divided into with and without respiratory problems. The variables were knowledge and attitudes towards sun exposure related to vitamin D deficiency risk, with data collection using a questionnaire. The result showed that the level of knowledge (98.31%) and attitude (100%) was low. There was no significant difference in the level of knowledge p-value (0.161 > 0.05) between with and without respiratory problems. The correlation test of knowledge and attitudes towards sun exposure related to the risk of vitamin D deficiency cannot be carried out because there was no excellent attitude. Knowledge and attitudes towards sun exposure related to the risk of vitamin D deficiency tend to be low in construction workers. However, knowledge and attitude were not the main factors affecting lung function.